2007
DOI: 10.1530/rep-06-0099
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chromatin and chromosome morphology by histone H3 modifications in pig oocytes

Abstract: Oocyte growth, maturation, and activation are complex processes that include transcription, heterochromatin formation, chromosome condensation and decondensation, two consecutive chromosome separations, and genomic imprinting. The objective of this study was to investigate changes in histone H3 modifications in relation to chromatin/chromosome morphology in pig oocytes during their growth, maturation, and activation. During the growth phase, histone H3 was acetylated at lysines 9, 14, and 18 (K9, K14, and K18)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 31 publications
6
81
1
Order By: Relevance
“…Our data on mouse antral oocytes are in agreement with those described before in pig [2] and show that once established during oocyte growth [10], this epigenetic signature is maintained, although its pattern of localisation changes during the stages of the NSN-to-SN transition: From a diffused distribution in NSN oocytes to the association with constitutive heterochromatin and then to the nucleolar surface region in SN oocytes.…”
Section: Resultssupporting
confidence: 91%
“…Our data on mouse antral oocytes are in agreement with those described before in pig [2] and show that once established during oocyte growth [10], this epigenetic signature is maintained, although its pattern of localisation changes during the stages of the NSN-to-SN transition: From a diffused distribution in NSN oocytes to the association with constitutive heterochromatin and then to the nucleolar surface region in SN oocytes.…”
Section: Resultssupporting
confidence: 91%
“…27,33 Low expression of phosphorylated H3/Ser10 and 28 were detected in GV oocytes. Following gradual dephosphorylation from GV to L-GV stage, a transient phosphorylation of H3/Ser10 at the periphery of condensed chromatin was reestablished at early GVBD stage (E-GVBD), and then the dramatically increased signals covered whole chromosomes from Pre-MI to MII.…”
Section: Changes In Histone Modifications During Mammalian Oocyte Matmentioning
confidence: 95%
“…1). [25][26][27] First, the acetylation levels of six lysine residues mentioned above were uniformly decreased at the late GV (L-GV) stage, indicating that histone deacetylation may be required for the orderly progression through GV to GVBD. Second, H4/K5 and H4/K16 were completely deacetylated in MI oocytes, and after transient reacetylation in anaphase I (AI), they were dramatically deacetylated again at MII chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…3; 2-6 hr). Recently Bui et al reported that the phosphorylation/dephosphorylation of histone H3 is the key event in chromosome condensation and decondensation in oocytes (Bui et al, 2007). For analyzing chromosome condensation and decondensation, we used histone phosphorylation at serine 10 (p-H3-S10).…”
Section: Chromosome Remodeling After Electrofusionmentioning
confidence: 99%